Variability of Inverted Repeats in All Available Genomes of Bacteria - Porubiaková, Otília; Havlík, Jan; Indu; Šedý, Michal; Přepechalová, Veronika; Bartas, Martin; Bidula, Stefan; Šťastný, Jiří; Fojta, Miroslav; Brázda, Václav (Microbiology spectrum, 2023)
Noncanonical secondary structures in nucleic acids have been studied intensively in recent years. Important biological roles of cruciform structures formed by inverted repeats (IRs) have been demonstrated in diverse organisms, including humans. Using Palindrome analyser, we analyzed IRs in all accessible bacterial genome sequences to determine their frequencies, lengths, and localizations. IR sequences were identified in all species, but their frequencies differed significantly across various evolutionary groups. We detected 242,373,717 IRs in all 1,565 bacterial genomes. The highest mean IR frequency was detected in the Tenericutes (61.89 IRs/kbp) and the lowest mean frequency was found in the Alphaproteobacteria (27.08 IRs/kbp). IRs were abundant near genes and around regulatory, tRNA, transfer-messenger RNA (tmRNA), and rRNA regions, pointing to the importance of IRs in such basic cellular processes as genome maintenance, DNA replication, and transcription. Moreover, we found that organisms with high IR frequencies were more likely to be endosymbiotic, antibiotic producing, or pathogenic. On the other hand, those with low IR frequencies were far more likely to be thermophilic. This first comprehensive analysis of IRs in all available bacterial genomes demonstrates their genomic ubiquity, nonrandom distribution, and enrichment in genomic regulatory regions. IMPORTANCE Our manuscript reports for the first time a complete analysis of inverted repeats in all fully sequenced bacterial genomes. Thanks to the availability of unique computational resources, we were able to statistically evaluate the presence and localization of these important regulatory sequences in bacterial genomes. This work revealed a strong abundance of these sequences in regulatory regions and provides researchers with a valuable tool for their manipulation.
Keywords: bacteria domain; DNA Replication; genomika; fylogeneze; bacterial genome analysis; inverted repeats; Palindrome analyser; lidé; Base Sequence; Phylogeny; Bacteria; Humans; sekvence nukleotidů; replikace DNA; Genomics